Antimicrobial Prescribing Practices at Dermatology Outpatient Departments in Tertiary Care Hospitals: A Multi-Centered, Cross Sectional Study (IAHS Medical Journal, 2022)
Background: An antimicrobial is an agent, that kills micro organisims or prevents their growth. The purpose of this study is to evaluate antimicrobial prescribing behaviors in the Dermatology Outpatient Department.Materials and methods: This multi-centered, cross-sectional study was conducted at Dermatology Outpatient Department of three tertiary care hospitals in Chattogram division, Bangladesh during the period October, 2021 to April, 2022.Results: During the study period, 463 prescriptions were obtained. Over half of the participants were female (57%) and between the ages of 21 to 40 years. The majority of patients were diagnosed with eczema (19%), acne (17%) and scabies (15%). Most commonly prescribed antimicrobials was Azithromycin (22%) followed by Permethrin (16%) and Erythromycin (7%). In most cases, antimicrobials were recommended for more than two weeks (60%). Nearly half of the antimicrobials (53 %) were recommended as combination of systemic and topical route.Conclusion: Current study found that dermatologists frequently recommended broad-spectrum antimicrobials for extended periods of time, which may lead to antimicrobial resistance. There is a need for continuing medical education on the appropriate use of antimicrobials, which will result in the effective management of skin diseases.IAHS Medical Journal Vol 5(1), June 2022; 16-21